Role of special breathing techniques in current physiotherapy practice for chronic obstructive pulmonary diseases - Savchenko, Valentyn M. (Journal of Education, Health and Sport, 2018)
The article determines the role of special breathing techniques in current physiotherapy practice for chronic obstructive pulmonary disease (COPD) taking into account scientific sources. The research is based on the scientific sources selected from electronic databases of the Vernadsky National Library of Ukraine, the Russian Scientific Electronic Library "eLibrary", Web of Science, PubMed, PEDro over the resent 10 years. Special breathing techniques include exercises for respiratory muscles (respiratory gymnastics) and airway clearance techniques (lung clearance: manual percussion and vibration, postural drainage, controlled coughing, autogenic drainage, and active cycle of breathing techniques). Most physiotherapists prescribe physical exercises (169/189, 89 %), forced expiratory technique (153/189, 81 %) and active cycle of breathing techniques (149/189, 79 %). There is currently no convincing evidence of the clinical and rehabilitation efficiency of the use of special breathing techniques. Further scientific research should be undertaken to identify the evidence of the role of special breathing techniques in physiotherapy practice for COPD.